Dynamics of Outgassing and Plume Transport Revealed by Proximal Unmanned Aerial System (UAS) Measurements at Volcán Villarrica, Chile. (5th February 2019) - Liu, Emma J.; Wood, Kieran; Mason, Emily; Edmonds, Marie; Aiuppa, Alessandro; Giudice, Gaetano; Bitetto, Marcello; Francofonte, Vincenzo; Burrow, Steve; Richardson, Thomas; Watson, Matthew; Pering, Tom D.; et al.
Abstract: Volcanic gas emissions are intimately linked to the dynamics of magma ascent and outgassing and, on geological time scales, constitute an important source of volatiles to the Earth's atmosphere. Measurements of gas composition and flux are therefore critical to both volcano monitoring and to determining the contribution of volcanoes to global geochemical cycles. However, significant gaps remain in our global inventories of volcanic emissions, (particularly for CO2, which requires proximal sampling of a concentrated plume) for those volcanoes where the near‐vent region is hazardous or inaccessible. Unmanned Aerial Systems (UAS) provide a robust and effective solution to proximal sampling of dense volcanic plumes in extreme volcanic environments. Here we present gas compositional data acquired using a gas sensor payload aboard a UAS flown at Volcán Villarrica, Chile. We compare UAS‐derived gas time series to simultaneous crater rim multi‐GAS data and UV camera imagery to investigate early plume evolution. SO2 concentrations measured in the young proximal plume exhibit periodic variations that are well correlated with the concentrations of other species. By combining molar gas ratios (CO2 /SO2  = 1.48–1.68, H2 O/SO2  = 67–75, and H2 O/CO2  = 45–51) with the SO2 flux (142 ± 17 t/day) from UV camera images, we derive CO2 and H2 O fluxes of ~150 t/day and ~2, 850 t/day, respectively. We observe good agreement between time‐averaged molar gas ratios obtained from simultaneous UAS‐ and ground‐based multi‐GAS acquisitions. However, the UAS measurements made in the young, less diluted plume reveal additional short‐term periodic structure that reflects active degassing through discrete, audible gas exhalations. Key Points: We present high‐resolution gas compositional data acquired using a multirotor Unmanned Aerial System (UAS) at Volcán Villarrica, Chile We derive SO2, CO2, and H2 O fluxes of ~162, ~150, and ~2850 t/day, respectively UAS gas measurements made in the young, undiluted plume reveal short‐term periodic active degassing associated with audible gas exhalations